Desain dan Pengujian Pengaplikasian Omron CP1L sebagai Remote Emergency Shutdown pada Aset Cementing - Siburian, Christian; Akhiriyanto, Novan; Ardianto, Valentino (Elposys: Jurnal Sistem Kelistrikan, 2024)
PT. X, an oil and gas service company in Indonesia, has a client facing safety risks at one of PT Y’s cementing assets. The client requested the implementation of an emergency shutdown component to mitigate the risk of accidents at the site. The primary challenge was the potential operational safety failures during cementing operations, which could lead to serious incidents without additional safety measures. This study aims to design and implement an emergency shutdown system based on the Omron CP1L to enhance operational safety at the cementing asset. The RES system was developed through a process of requirement identification, design, integration, and testing, supported by relevant literature studies. The system’s design includes the selection of appropriate hardware and software, as well as the development of logic to execute the shutdown when PT Y’s crew presses the emergency push button. Testing results indicate that the RES functions with an average delay time ranging from 1.5 to 1.9 seconds. The conclusion from this study is that the RES system is effective in enhancing operational safety and minimizing risks at PT Y’s cementing asset.